Fingerboard Media Development Calculate for the Cognitive Improvement of Teachers at RA Muslimat NU 1 Tulus Rejo - Dewi Maftutah; Siti Roudhotul Jannah; Ferdian Utama (Journal of Childhood Development, 2021)
The development of media as a tool to improve children's development, especially at the early childhood education level, is very important. The assistance of media or educational play tools in children's activities at school is directly proportional to the slogan of playing while learning. This article aims to explain about letter board media assistance for PAUD teachers in schools, as well as children's cognitive enhancement through counting board media. The data used were obtained from observations, interviews, tests and interviews. This article finds that the development of finger pad media makes it easier for teachers as well as aids in children's cognitive enhancement. The finger board media used by the teacher has an impact on the joy of children with the media used. This article strengthens some of the previous articles about cognitive enhancement in children assisted by fun fingertip media.